2016
DOI: 10.1074/jbc.m116.736850
|View full text |Cite
|
Sign up to set email alerts
|

The Lipidated Peptidomimetic Lau-((S)-Aoc)-(Lys-βNphe)6-NH2 Is a Novel Formyl Peptide Receptor 2 Agonist That Activates Both Human and Mouse Neutrophil NADPH Oxidase

Abstract: Neutrophils expressing formyl peptide receptor 2 (FPR2) play key roles in host defense, immune regulation, and resolution of inflammation. Consequently, the search for FPR2-specific modulators has attracted much attention due to its therapeutic potential. Earlier described agonists for this receptor display potent activity for the human receptor (FPR2) but low activity for the mouse receptor orthologue (Fpr2), rendering them inapplicable in murine models of human disease. Here we describe a novel FPR2 agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…This receptor is expressed in a variety of cell types, such as endothelial cells, neutrophils, and macrophages . Much is known about the proinflammatory functions of neutrophils; however, a more recent work suggests that neutrophils expressing ALX/FPR2 play a key role in host defense and resolution of inflammation . Here, we hypothesize that hemin can regulate ALX/FPR2 expression, resulting in impairment of neutrophils pro‐resolution responses triggered by ALX/FPR2 agonist.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This receptor is expressed in a variety of cell types, such as endothelial cells, neutrophils, and macrophages . Much is known about the proinflammatory functions of neutrophils; however, a more recent work suggests that neutrophils expressing ALX/FPR2 play a key role in host defense and resolution of inflammation . Here, we hypothesize that hemin can regulate ALX/FPR2 expression, resulting in impairment of neutrophils pro‐resolution responses triggered by ALX/FPR2 agonist.…”
Section: Discussionmentioning
confidence: 86%
“…Lipoxin A 4 receptor (ALX)/formyl peptide receptor 2 (FPR2) acted as a pivotal checkpoint in host defense, inhibited the recruitment of PMNs into the inflamed site, and promoted PMN apoptosis by recognizing pro‐resolving mediators, such as lipoxin A 4 , resolvin D1 (RvD1), and annexin A1 . A more recent work suggests that neutrophils expressing ALX/FPR2 play a key role in the resolution of inflammation and immune regulation . Dufton et al found that the inhibition of PMN recruitment by annexin A1 was attenuated largely in Fpr2 −/− (the murine homologue of ALX/FPR2) mice, leading to greater acute inflammation and a prolongation of inflammatory arthritis.…”
mentioning
confidence: 99%
“…Out of the eight murine members of the Fpr gene family, the Fpr1 and Fpr2 are most similar to the human receptors both when it comes to sequence similarities, expression patterns, and functional properties [7]. It should be noticed that until recently no formylated peptide had been shown to activate FPR2/Fpr2, but it is now clear that PSMα peptides are specifically recognized by these receptors [12, 14, 24, 32]. We know now that FPR2 displays also binding affinity for formyl peptides, but the peptide size matters, i.e., large formyl peptides prefer FPR2 whereas short formyl peptides have high affinity for FPR1 [12, 13, 33].…”
Section: Discussionmentioning
confidence: 99%
“…We also recently showed that some of the most potent and selective antagonists for the human FPRs lack effects on their mouse counterparts, cyclosporin H and PBP 10 being prominent examples [ 12 ]. We have also identified lipidated peptidomimetics and a set of formylated MHC class Ib binding peptides as novel agonists for both human and mouse receptors, but there were no direct correlations between the activities induced by these agonists in human and mouse neutrophils [ 13 , 14 ]. This clearly implies that when comparing mice and men there are some similarities between the receptor orthologous in the two species, but there are also important differences in the ligand recognition profiles.…”
Section: Introductionmentioning
confidence: 99%